The health a biopsychosocial approach to discussing student health issues: current trends in foreign research - Minnikaeva, N.V.; Melnikova, T.I.; Vinogradova, O.P.; Butakova, E.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the problem field of research into student health from the standpoint of a biopsychosocial approach. Methods and structure of the study. The methodological basis of the study consisted of theoretical analysis and the systematisation of data from contemporary foreign publications (a total of 16 scholarly articles). Results and conclusions. Studies have shown a high prevalence of psychological problems among students. The COVID-19 pandemic has aggravated the situation: up to 63.4% of students reported a deterioration in mental health during distance learning. The reasons for the deterioration in students’ health have been generalised: low motivation – 65.4%, insufficient family involvement – 22.7%, ineffectiveness of the educational process – 11.9%. It is possible to improve students’ health on the basis of physical activity, mediated by psychosocial mechanisms: self-efficacy, enjoyment of activities and social support. The analysis of foreign publications confirms the universality of the health problems of students from different countries and the necessity of integrating digital technologies and pedagogical strategies for effective health-formation in higher education institutions on the basis of a biopsychosocial approach.